Ultra-Processed Foods and Nutritional Intake of Children and Adolescents from Cantagalo, São Tomé and Príncipe - Morais, R. (2024)
Background: Globally, dietary patterns are shifting toward an increased consumption of ultra-processed foods, raising the risk of some metabolic and nutritional diseases from a young age. This trend is now also affecting low- and middle-income countries. Considering this, we aimed to assess the contribution of ultra-processed foods to total energy intake and their association with the nutritional intake of children and adolescents in Cantagalo, S & atilde;o Tom & eacute; and Pr & iacute;ncipe. Methods: We conducted a cross-sectional study with a sample of 546 households. Data were collected on anthropometrics, sociodemographic characteristics, and lifestyle, including 24 h food recall questionnaires for children and adolescents. The reported foods were nutritionally assessed and categorized according to the NOVA classification to estimate the contribution of ultra-processed foods. Logistic regression models were used to estimate the magnitude of the associations between higher consumption of ultra-processed foods and nutritional intake, adjusting for confounders. Results: The contribution of ultra-processed foods to daily energy intake was 9.5% for girls and 8.5% for boys. Higher consumption of ultra-processed foods was significantly associated with a lower intake of fiber (OR = 0.932; 95%CI, 0.872-0.996), vitamin B12 (OR = 0.812; 95%CI, 0.668-0.985), and zinc (OR = 0.443; 95%CI, 0.308-0.639) and a higher intake of iron (OR = 1.479; 95%CI, 1.065-2.055) and sodium (OR = 1.001; 95%CI, 1.000-1.001), after adjusting for confounders. Conclusion: Higher consumption of ultra-processed foods was especially associated with a lower intake of fiber, vitamin B12, and zinc, and with a higher intake of iron.